Covid-19 hastalarında erken uyarı skorlamalarının prognozu öngörmedeki rolü - Özpınar, Yasin (İstanbul Medipol Üniversitesi Tıp Fakültesi, 2021)
Amaç; Koronavirüs Hastalığı 2019(COVID-19) hastalarının prognozunu öngörmek ve tirajının hızlı ve kolay yöntemlerle yapılması büyük önem arz etmektedir. Bu çalışmada 5 erken uyarı skorundan hangisinin COVID-19 hastalarında prognozu daha isabetli tahmin edeceğinin belirlenmesi amaçlandı. Metot: 11 Mart 2020 ile 1 Ocak 2021 tarihleri arasında İstanbul Medipol Üniversitesi Tıp Fakültesi Medipol Mega Hastanesinde COVID-19 nedeni ile serviste yatırılarak takip edilen 18 yaş üzeri 861 hasta çalışmaya dahil edildi. Hastaların yatış anındaki ilk vital değerlendirmeleri ve bilinç durumu değerlendirmeleri kullanılarak Ulusal Erken Uyarı Skoru(NEWS), Modifiye Erken Uyarı Skoru(MEWS), Hızlı Acil Tıp Skoru(REMS), Tekrarlanan-Sepsis İlişkili Organ Yetmezliği Hızlı Değerlendirmesi(q-SOFA) ve Acil Serviste Triyaj Erken Uyarı Skoru (TREWS) hesaplandı ve 30 gün içinde ölüm durumu veya 15 gün içinde yoğun bakım ihtiyacı açısından retrospektif olarak incelendi. Skorların prognozu öngörmedeki performanslarını değerlendirmek için Alıcı İşletim Karakteristiği(ROC) analizi yapıldı. Her bir skor için Youden İndeks'ine göre eşik değer belirlendi ve duyarlılık, özgüllük, pozitif prediktif değer, negatif prediktif değer hesaplandı. Bulgular: 30 gün içinde ölüm durumunu ve 15 gün içinde yoğun bakım ihtiyacını öngörmede REMS en başarılı skor olarak bulunurken TREWS ve NEWS de benzer performans sergiledi. Ancak MEWS ve q-SOFA'nın her iki durumu da öngörme performansı yetersiz bulundu. 30 gün içinde ölüm durumunu öngörmek adına REMS, TREWS, NEWS, MEWS ve q-SOFA için sırasıyla % 95 güven aralığında(GA) eğri altında kalan alan(EAKA) 0.733 (% 95GA, 0.676-0.789), 0.719 (% 95GA, 0.659-0.780), 0.694 (% 95GA, 0.629-0.759), 0.564 (% 95GA, 0.491-0.637), 0.563 (% 95GA, 0.488-0.638) olarak hesaplandı. 15 gün içinde yoğun bakım ihtiyacını öngörmek adına REMS, TREWS, NEWS, MEWS ve q-SOFA için sırasıyla EAKA 0.693 (% 95GA, 0.633-0.752), 0.666 (% 95GA, 0.606-0.725), 0.637 (% 95GA, 0.574-0.701), 0.534 (% 95GA, 0.471-0.598), 0.538(% 95GA, 0.473-0.602) olarak hesaplandı. REMS, TREWS ve NEWS'in her iki durumu da öngörme açısından negatif prediktif değerleri % 90'nın üzerinde hesaplandı. Sonuç: Sonuç olarak COVID-19 hastalarında prognozu öngörmek için REMS, TREWS ve NEWS kullanılabilir ancak MEWS ve q-SOFA etkisiz bulunmuştur. Ayrıca etkili bulunan bu 3 erken uyarı skoru, yüksek negatif prediktif değerleri sayesinde kötü prognoz açısından düşük riskli COVID-19 hastalarını belirlemekte kullanılabilir.

Aims: It's very important to predict the prognosis and triage of Coronavirus Disease 2019(COVID-19) quickly and easily. In this study, it's aimed to determine which of the 5 early warning scores would predict the prognosis more accurately in COVID-19 patients. Method: Between 11.03.2020 and 01.01.2021, 861 patients over the age of 18 who were hospitalized and followed up due to COVID-19 in Istanbul Medipol University Faculty of Medicine Medipol Mega Hospital were included in the study. National Early Warning Score(NEWS), Modified Early Warning Score(MEWS), Rapid Emergency Medicine Score(REMS), Quick Sequential-Sepsis Related Organ Failure Assessement(q-SOFA), Triage in Emergency Department Early Warning Score(TREWS) were calculated using the patients' first vital signs and consciousness levels at the time of hospitalization, and they were analyzed in terms of death within 30 days or need for intensive care within 15 days retrospectively. Receiver operating characteristic(ROC) analysis was performed to evaluate the performance of the scores in predicting prognosis. For each score, the threshold value was determined according to Youden Index, and sensitivity, specificity, positive predictive value, and negative predictive value were calculated. Results: REMS was found to be the most successful score in predicting death within 30 days and intensive care need within 15 days, while TREWS and NEWS performed similarly. However, the predictive performances of MEWS and q-SOFA were found to be inadequate for both situations. In order to predict mortality within 30 days, the area under the curve(AUC) at 95% confidence interval(CI) for REMS, TREWS, NEWS, MEWS and q-SOFA were calculated as 0.733 (95% CI, 0.676-0.789), 0.719 (95% CI, 0.659-0.780), 0.694 (95% CI, 0.629-0.759), 0.564 (95% CI, 0.491-0.637), 0.563 (95% CI, 0.488-0.638), respectively. The AUC for the REMS, TREWS, NEWS, MEWS and q-SOFA in predicting admission to the intensive care unit within 15 days were calculated as 0.693 (95% CI, 0.633-0.752), 0.666 (95% CI, 0.606-0.725), 0.637 (95% CI, 0.574-0.701), 0.534 (95% CI, 0.471-0.598), 0.538 (95% CI, 0.473-0.602) respectively. The negative predictive values of REMS, TREWS and NEWS were over the 90% in terms of predicting both situation. Conclusion: In conclusion, REMS, TREWS and NEWS could be used to predict prognosis in COVID-19 patients, but MEWS and q-SOFA were found to be ineffective. In addition, due to the high negative predictive values of these 3 early warning scores, it could be useful to identify low risk COVID-19 patients for poor prognosis.
The role of early warning scores in predicting prognosis in Covid-19 patients
Keywords: COVID-19; Prognoz; REMS; TREWS; NEWS; MEWS; q-SOFA; COVID-19; Prognosis; REMS; TREWS; NEWS; MEWS; q-SOFA